2022
DOI: 10.1186/s12871-022-01924-x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of epidural anesthesia via the intervertebral foramen approach in percutaneous transforaminal endoscopic discectomy: a retrospective study

Abstract: Background Satisfactory intraoperative analgesia is critical for percutaneous transforaminal endoscopic discectomy (PTED). Local anesthesia (LA) and epidural anesthesia (EA) are recommended for PTED. LA alone does not achieve satisfactory pain management during PTED and other analgesics or sedatives are usually needed. Traditional EA, which involves implanting an epidural catheter through the midline or paramedian, has disadvantages such as difficulty in catheterization and increased preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…In a study, females comprised the majority of the sample. (9). Exploring the epidural space of the TFESI is somewhat challenging in a significantly deteriorated and constricted foramen.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, females comprised the majority of the sample. (9). Exploring the epidural space of the TFESI is somewhat challenging in a significantly deteriorated and constricted foramen.…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Zhang et al included 160 PTED candidates and divided them into two groups, one receiving transforaminal EA and the other LA (28). They showed that the satisfaction rate and lumbar and leg VAS scores were significantly lower in the transforaminal EA group (28).…”
Section: Discussionmentioning
confidence: 99%
“…In 2022, Zhang et al included 160 PTED candidates and divided them into two groups, one receiving transforaminal EA and the other LA (28). They showed that the satisfaction rate and lumbar and leg VAS scores were significantly lower in the transforaminal EA group (28). A systematic review conducted by Zhen et al also confirmed that the satisfaction rate is statistically higher among patients who received EA (26).…”
Section: Discussionmentioning
confidence: 99%
“…No additional benefits were seen when preinduction administration of ITM by an anesthesiologist was compared with intraoperative administration by surgeons 66 . Epidural single-injection analgesia has been reported for percutaneous transforaminal endoscopic discectomy, where the surgeon injects the drug through a transforaminal approach under fluoroscopic guidance 67 . Single-injection epidural injections, whether performed by an anesthesiologist preinduction 68 or a surgeon intraoperatively, 69 have shown decreased LOS in addition to pain relief and patient satisfaction.…”
Section: Enhanced Recovery After Surgery and Multimodal Analgesiamentioning
confidence: 99%
“…Erector spinae plane block [47][48][49][50][51][52][53] Most studied block in adult spine surgeries Associated with reduced opioid consumption intraoperatively and postoperatively, lower pain scores, less NV and better patient satisfaction More comparative effectiveness studies are required Most studied block in pediatric spine surgeries Associated with reduced opioid consumption intraoperatively and postoperatively, lower pain scores, less NV and better patient satisfaction More comparative effectiveness studies are required Thoracolumbar interfascial plane block [56][57][58][59] Limited studies with mixed results Not studied Midpoint transverse process to pleura block 45,46 Inadequate data Not studied Quadratus lumborum block 60 Single retrospective study Can be used for anterior and posterior approach lumbar spine surgeries Not studied Surgical infiltration [67][68][69][70][71][72][73][74]…”
Section: Not Studiedmentioning
confidence: 99%